Persepsi ibu hamil trimester III terhadap hubungan senam yoga dalam mengurangi kecemasan di sekolah emak ( yayasan ibu sejati indonesia ) medan permai, kelurahan medan tuntungan kota medan - Juniar Alpina Br sitorus (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
Pregnancy is a time when a woman carries an embryo or fetus in her body, at the time of pregnancy the mother has the perception that childbirth is frightening, and has anxiety, to overcome this problem, namely yoga exercises, the purpose of this study is to determine the perceptions of pregnant women in trimester. III regarding yoga exercises in reducing anxiety in the mother school, the Indonesian True Mother Foundation, Medan, Medan, Medan, in 2020. This type of research is a descriptive study with a qualitative approach, the sample in this study amounted to twelve people, consisting of ten pregnant women, one Chairperson of the Mother School Foundation of the Indonesian True Mother Foundation, and one Yoga Gymnastics Coach at the mother's school foundation. true mother of Indonesia. The results of this study, that doing yoga exercises can reduce anxiety in the face of childbirth, reducing anxiety is because during yoga exercise mothers are prepared to face childbirth by exercising muscle control, breathing techniques, relaxation and practicing peace of mind. Pregnant women say that before doing yoga exercises, mothers feel anxiety so that yoga exercises are needed to reduce anxiety in facing childbirth. Yoga exercise also has useful meditation techniques to help calm the mind, reducing stress yoga has the benefit of reducing stress. Suggestion For the research site, it is hoped that the research site will provide a forum for health workers, especially midwives, to take part in yoga exercise training so that midwives can apply yoga exercises to classes for pregnant women. Keywords: Perception, Anxiety, Yoga, pregnant women